2017
DOI: 10.1186/s12889-017-4404-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the mammography self-efficacy and fear of breast cancer scales in Iranian women

Abstract: BackgroundResearch investigating mammography screening has often reported low mammography self-efficacy and breast cancer fear contribute to underutilization of mammography. This study aimed to examine the reliability and validity of Champion’s Mammography Self-efficacy Scale (CMSS) and Champion’s Breast Cancer Fear Scale (CBCFS) in a sample of Iranian women.MethodsThe adapted instruments were administered to a community sample of 482 women aged 40 years or older. They inhibited in Sanandaj, Iran. Cronbach’s α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…All of the items worked well in the analyses, as indicated by their high item-total correlations with the overall score and strong relationship with the latent factor; the scale as a whole also worked well, as indicated by its high internal consistency and test-retest reliability. The results of the CFA were congruent with the one-factor structure obtained by Champion et al [ 10 ] in their study of development of the CBCFS, as well as with other adaptation studies [ 15 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All of the items worked well in the analyses, as indicated by their high item-total correlations with the overall score and strong relationship with the latent factor; the scale as a whole also worked well, as indicated by its high internal consistency and test-retest reliability. The results of the CFA were congruent with the one-factor structure obtained by Champion et al [ 10 ] in their study of development of the CBCFS, as well as with other adaptation studies [ 15 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…The CBCFS has been used in many studies and validated in several cultures. The original one-factor structure of this scale was replicated by Moshki et al [ 15 ] in a sample of Iranian women; however, a two-factor structure was obtained by Secginli [ 16 ] in a sample of Turkish women. The CBCFS was also adapted to assess fear of colorectal cancer in a Chinese sample [ 17 ], where the one factor structure was also supported.…”
Section: Introductionmentioning
confidence: 99%
“…The instruction material was prepared by a reliable, pertinent team; and consisted of easy-tounderstand, attractive messages that had shown effective regarding their scienti c content and instructive effect, and satisfactory to most patients in a previous study (Boroumand Sani et al Forthcoming). BCF and worry were assessed by standard validated tests [14,15,16,17], and the general psychological health of all participants was accredited before and after the intervention by a validated test (HADS). This precise design has shown that giving useful information about BC can effectively reduce the fear and worries of healthy women about the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The next seven questions were the Champion BC fear scale. This standard validated scale consists of eight questions [16], however in the Farsi translation the two last questions have been merged (resulting in seven questions) after undergoing validation and reliability tests by Moshki et al [17]. The last fourteen questions consisted of the hospital anxiety and depression scale (HADS) [18].…”
Section: Interventions Measurements and Testsmentioning
confidence: 99%
“…These items evaluated the perception of people for whom the individual could rely on to obtain information about obtaining a mammography. Psychosocial barriers to receiving mammography screening include worry, pain, shame, feelings of being too old to be screened, and fear [ 50 ]. Overcoming these barriers consequently may affect the extent to which someone relied on others’ support [ 3 , 20 ].…”
Section: Discussionmentioning
confidence: 99%